The Impact of Social Media Marketing and Shopee Live Streaming on Millennial Women's Impulse Buying - Dhani Aprilianti; Umi Narimawati; M. Yani Syafei (Dinasti Publisher, 2025)
The increasing development of digitalization in marketing is further driving the use of Social Media Marketing and Live Streaming as key strategies in enhancing impulse buying. This research aims to analyze the influence of these two variables on consumers' impulsive purchasing decisions. Employing a quantitative method, this study involved 110 female millennial respondents in Bogor City. Data were collected through questionnaires and analyzed using multiple linear regression tests. The research results indicate that Social Media Marketing has a positive and significant influence on impulse buying (t-statistic = 2.426; p = 0.017). This suggests that attractive and interactive marketing strategies on social media can encourage spontaneous purchasing decisions. Furthermore, Live Streaming was also proven to contribute significantly to increasing impulse buying (t-statistic = 2.283; p = 0.024). The trustworthiness dimension emerged as the dominant factor in the effectiveness of live streaming, where the higher the level of consumer trust in the seller, the greater the likelihood of them making impulsive purchases. The simultaneous test results (F-test) show that the combination of Social Media Marketing and Live Streaming together significantly influences impulse buying (F-statistic = 10.794; p = 0.000). However, the R-Square value of 0.157 indicates that these two variables only explain 15.7% of the variability in impulse buying, while the remaining 84.3% is influenced by other factors such as discounts, product quality, and consumer psychological aspects. These findings provide implications for business actors to optimize digital marketing strategies to increase impulsive purchases. Future research is expected to explore additional factors and expand the respondent scope to gain a deeper understanding of consumer behavior.